The Problems of Learning Javanese Speaking Skills Among Generation Z High School Students - Adi Sulistyo; Endang Nurhayati (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2026)
Learning to speak Javanese for Generation Z high school students faces various challenges amidst social and cultural changes. This study aims to analyze the problems of learning to speak Javanese for Generation Z students from linguistic and environmental perspective. Used a qualitative descriptive. The subjects consisted of grade 10 students and 1 Javanese language teacher at Taruna Nusantara Senior High School. Data were collected through questionnaires and interviews, then analyzed using Miles and Huberman interactive analysis model. The results showed that students motivation to learn speak Javanese was relatively high, as indicated by perceptions of the importance of speaking skills (92.9%), improving speaking skills (92.9%), and the usefulness of Javanese (87.5%). The main problems actually lie in the linguistic aspect, low mastery of phonology (46.4%), basic vocabulary (40.2%), sentence formation (37.5%), and use of speech levels (25.9%). Environmental perspective, dominant barriers include differences in mother tongues (75.0%), limited class hours (73.2%), a lack of native speakers in the community (63.4%), and the complexity of krama rules (76.8%). These findings imply the need for more communicative, contextual, and adaptive Javanese language learning aligns with the characteristics of Generation Z, with an emphasis on authentic language practice and strengthening basic linguistic competencies.